Managerial foresight and attempted rent appropriation: insider trading on knowledge of imminent breakthroughs - Ahuja, Gautam; Coff, Russell; Lee, Peggy M. (Strategic Management Journal, 2005)
Abstract In order to establish a competitive advantage, firms must acquire or create resources at a price below their value in use. Absent pure luck, this requires managers to exercise foresight about a resource's future value and/or complementarities with pre‐existing capabilities. This foresight grants managers the opportunity to exploit information asymmetries for personal gain as well as building organizational capabilities. Nevertheless, there is limited research on the extent of foresight or how managers use it. In our study of insider trading, we found that managers purchase stock well before breakthrough patents are filed. We argue for further research on the extent of managerial foresight and how it affects rent generation and appropriation. Copyright © 2005 John Wiley & Sons, Ltd.